Evaluation of Manual and Two-Rotary Niti Retreatment Systems in Removing Gutta-Percha Obturated with Two Root Canal Sealers. (10th September 2012) - Jayasenthil, Athikesavan; Sathish, Emmanuel Solomon; Prakash, Prashanth
Abstract : Objective . The objective of this study was to evaluate the efficacy of two retreatment NiTi systems (protaper universal retreatment files, R-Endo), when compared to manual technique in removing Gutta-percha obturated with two sealers. Study Design . Sixty extracted single-rooted premolars were instrumented with Protaper rotary files till F3. The specimens were divided into six groups. Groups 1, 2, 3 were obturated with Gutta-percha and zinc oxide eugenol and Groups 4, 5, 6 were obturated with Gutta-percha and AH-plus. The retreatment was carried out in groups 1 and 4 with H-files and GGdrills, groups 2 and 5 with R-endo retreatment files and groups 3 and 6 with Protaper retreatment files. The roots were sectioned and evaluated under optical stereomicroscope. Statistical analysis was performed with one-way ANOVA and Newman-Keul's test at P < 0.05 . Results . The manual technique resulted in cleaner canal walls when compared with both rotary retreatment systems. Conclusion . NiTi rotary retreatment files can be used to remove the filling material quickly, but it should be followed by hand instruments to obtain better canal wall cleanliness.